A Case Report of Sanguis Draconis for Treating a Patient With Refractory Wound Dehiscence After Breast Cancer Chemotherapy. Issue 1 (January 2016) - Zhang, Guizhen; Hua, Yafang; Jin, Xueqin; Yan, Chunmei
Abstract : Breast cancer is one of the most common female malignant tumors. According to data statistics, the incidence of breast cancer was 7% to 10% for a variety of malignant tumors, being only lower than that of uterine cancer. The methods of treating breast cancer are given priority over operative treatment and combined with chemotherapy and radiotherapy. However, exosmosis of chemotherapeutic drugs is a common complication of chemotherapy. Exosmosis of drugs can stimulate local organs to induce acute inflammatory reaction and necrosis, which finally lead to wound infection and difficulty in healing. In December 2013, a patient with full-thickness wound (an area of 5 × 3 cm) dehiscence at the completion of the second phase of chemotherapy for left breast cancer after radical operation was admitted to our department. Her wound had healed after radical operation. The patient followed an integrative therapy treatment protocol that consisted of an external application of a phytomedicine called Sanguis Draconis and combined with a series of conventional treatments, including 3M Transparent Dressing moist therapy, increase in nutrition, and prevention therapies for infection. The patient's integrative treatment program resulted in complete wound healing, and the successful completion of the late 6 courses of chemotherapy. The article describes the nursing experiences associated with this case study.